Aqueous microwave-assisted cross-coupling reactions applied to unprotected nucleosides - Hervé, Gwénaëlle; Len, Christophe (Frontiers in Chemistry, 2015)
Nucleoside analogues have attracted much attention due to their potential biological activities. Amongst all synthetic nucleosides, C5-modified pyrimidines and C7- or C8-modified purines have mostly been prepared using palladium cross-coupling reactions and then studied as antitumoral and antiviral agents. Our objective is to focus this review on the Suzuki-Miyaura and on the Heck cross-couplings of nucleosides using microwave irradiations which are an alternative technology compatible with green chemistry and sustainable development.